Smooth Operator: Tuning Robot Perception Through Artificial Movement Sound - Robinson, Frederic Anthony; Velonaki, Mari; Bown, Oliver (2021 16th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2021)
Can we influence how a robot is perceived by designing the sound of its movement? Drawing from practices in film sound, we overlaid a video depicting a robot's movement routine with three types of artificial movement sound. In a between-subject study design, participants saw either one of the three designs or a quiet control condition and rated the robot's movement quality, safety, capability, and attractiveness. We found that, compared to our control, the sound designs both increased and decreased perceived movement quality. Coupling the same robotic movement with different sounds lead to the motions being rated as more or less precise, elegant, jerky, or uncontrolled, among others. We further found that the sound conditions decreased perceived safety, and did not affect perceived capability and attractiveness. More unrealistic sound conditions led to larger differences in ratings, while the subtle addition of harmonic material was not rated differently to the control condition in any of the measures. Based on these findings, we discuss the challenges and opportunities regarding the use of artificial movement sound as an implicit channel of communication that may eventually be able to selectively target specific characteristics, helping designers in creating more refined and nuanced human-robot interactions.CCS CONCEPTS* Human-centered computing \rightarrowInterface design prototyping; Auditory feedback.